DEKOMPOSISI JERAMI PADI OLEH BIAKAN CAMPURAN BAKTERI SELULOLISIS DAN PENAMBAT NITROGEN(Suatu Percobaan Laboratorium) DECOMPOSITION OF RICE STRAW BY MIXED CULTURE OF CELLULOLYTIC AND NITROGEN FIXING BACTERIA(Laboratory Experiment) - Ekawati, Ida; , Syekhfani (Pembangunan Pedesaan, 2005)
The objective of this research was to know the ability of mixed culture of cellulolytic and nitrogen-fixing bacteria to increase decomposition rate of rice straw. A Completely Randomized Design with five replications was used in laboratory experiment. The treatments were a) synergetic cellulolytic bacteria (S2+S7), b) synergetic cellulolytic bacteria + Azotobacter, c) synergetic cellulolytic bacteria + Azospirillum, d) synergetic cellulolytic bacteria + Azotobacter + Azospirillum. The result showed that the nitrogen-fixing bacteria grown in mixed culture with cellulolytic bacteria could increase the decomposition rate of rice straw. This was proved by decreasing dry weight of the straw and higher decreasing of cellulose and lignin content than synergetic cellulolytic bacteria treatment. Mixed culture of synergetic cellulolytic and nitrogen-fixing bacteria showed that k (constant of the rate for decreasing total rice straw dry weight) was 0.0401 and k value for synergetic cellulolytic bacteria was only 0.0380.